Healthcare Professionals’ Preferred Efficacy Endpoints and Minimal Clinically Important Differences in the Assessment of New Medicines for Chronic Obstructive Pulmonary Disease - Dankers, Marloes; Nelissen-Vrancken, Marjorie H. J. M. G.; Surminski, Sara M. K.; Lambooij, Anke C.; Schermer, Tjard R.; van Dijk, Liset (Frontiers in Pharmacology, 2020)
Background Registration authorities evaluate effects of new medicines for chronic obstructive pulmonary disease (COPD) on airway obstruction, dyspnea, health status and exacerbations. To establish clinical relevance, minimal clinically important differences (MCIDs) are used. The aim of this study was to investigate which efficacy endpoints and MCIDs healthcare professionals consider clinically relevant for new COPD medicines. Materials and methods 7,731 Healthcare professionals received an electronic questionnaire. Participants were asked for: 1) preferred efficacy endpoints for new COPD medicines and 2) cut-off values defining clinical relevance for forced expiratory volume in 1 second (FEV1), Transition Dyspnea Index (TDI) and St. George's Respiratory Questionnaire (SGRQ). Those cut-off values were compared to the MCIDs used by registration authorities, namely 100 ml for FEV1, 1 unit for TDI and 4 units for SGRQ. Results 227 Healthcare professionals responded to the questionnaire. Most preferred efficacy endpoints were exacerbations (51.0%), airway obstruction (46.9%) and health status (44.9%). Mean cut-off values for TDI and SGRQ were significantly higher than the corresponding MCIDs, mean differences 1.5 (95%CI=1.3 – 1.8, p<0.001) and 7.0 (95%CI=5.1 – 8.8, p<0.001), respectively. The mean cut-off value for FEV1 was comparable to the MCID (mean difference 2.2, 95%CI=-19.9 – 24.3, p=0.84). Conclusions Healthcare professionals largely agree with efficacy endpoints used for the evaluation of new COPD medicines. However, they seem to prefer higher cut-off values for clinical relevance for TDI and SGRQ than the registration authorities. Effects of new medicines on TDI and SGRQ that are considered clinically relevant by registration authorities do, therefore, not necessarily reflect healthcare professionals’ perspectives on clinical relevance.